A Study on the Use of Child Restraint System (CRS) in Indonesia and Vietnam - Santosa, S.P.; Gunawan, L.; Jusuf, A.; Arifurrahman, F.; Akbar, I.; Anh, L.H.; Ab Rashid, A.A.; Abu Kassim, K.A.; Ahmad, Y. (Journal of the Society of Automotive Engineers Malaysia, 2020)
As technology develops in passenger vehicles, occupant safety is an issue that cannot be ignored, especially with regard to child occupants. Therefore, the child occupant safety should be given emphasis in the car assessment program to increase car safety levels and to primarily ensure children’s safety during travels. To this end, ASEAN NCAP through its child occupant protocol recommends the use of a Child Restraint System (CRS). This study evaluates the level of vehicle users’ awareness of the use of CRS (ownership and usage) in Indonesia and Vietnam. In this study, 336 Indonesian and 119 Vietnamese parents with children aged six years or below were asked to fill out the questionnaire both online and in written form. In Indonesia, the data showed that 70% of the participants owned CRS, while the rest either unrestrained or used the vehicle seat belts for their children. In Vietnam, 77% of the participants owned CRS. Moreover, there were approximately 26% respondents in Indonesia, and 9% in Vietnam who did not use the CRS. Parents did not use CRS for their children due to several reasons, namely children refusal and parents’ preference to place children on their lap. In Indonesia, only 58% of children used proper CRS according to their age group, and 35% of the parents installed CRS properly per the user manuals. In addition, more than 50% of the 28 surveyed vehicles in Indonesia were fitted with ISOFIX standard CRS attachment. Furthermore, it appears that there was high enthusiasm among parents to use CRS based on their willingness to pay for it. However, initiatives such as social awareness campaigns or even regulation should be considered to increase CRS usage both in Indonesia and Vietnam.